Kompresi Data Menggunakan Metode FELICS (Fast Efficient and Lossless Images Compression System) Terhadap Citra PNG (Portable Network Graphics) - Hutapea, Yan Daniel; Wulan, Nur (Forum Kerjasama Pendidikan Tinggi, 2024)
At present, the rapid advancement of sciens and information technology has made two-dimensional image files highly demanded. In this era, sending files, whether in text or image format, has become a common practice. Sending large image files requires more time and bandwidth. To address this, compression is necessary for image files. The FELICS method is one of the techniques that can be used for image file compression. FELICS present a simpler system for image compression, operates faster, and only inscurs minimal compression efficiency loss. Based on test results for five .png files with sizes of 5.249.494 bytes reduced to 2.041.208 bytes, 3.124.201 bytes reduced to 1.060.781 bytes, 10.473.459 bytes reduced to 3.065.010 bytes, 804.728 bytes reduced to 200.215 bytes, and 503.111 bytes reduced to 158.711 bytes. This results in compression retions ranging from 24.87% to 38.00%.